ILRI 40 years scene-setting address by H.E. Teferra Derebew, Minister of Agriculture, Ethiopia - Derebew, T. (International Livestock Research Institute, 2014)
Scene-setting address by H.E. Teferra Derebew, Minister of Agriculture, Ethiopia at the ILRI@40 Conference: Livestock-based options for sustainable food and nutritional security, economic well-being and healthy lives. ILRI@40 conference, Addis Ababa, Ethiopia, 6–7 November 2014.